Some features and problems of reforming of individual income tax in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article discusses the individual income tax as one of the main sources of state and local budgets. Also, the article describes the procedure and peculiarities of taxation of income of individuals according to the Tax Code of the Republic of Kazakhstan. The basic problems of taxation of income of citizens and prospects of using foreign experience in regulating it, suggestions for improvement of system of the individual income taxation are given.Key words: individual income tax, the income of an individual, the state budget, the general declaring of income and property, the progressive tax scale, source of payment, the tax rate.